The politics of gratitude versus defiance: failed emancipatory defiance and the restoration of asymmetric deference roles in Northern Cyprus - Azgin, Bilge; Kaymak, Erol (Routledge Journals, Taylor & Francis Ltd, 2025)
This paper analyses the dynamics of defiance within the patron-client relationship (PCR) between Turkey and northern Cyprus. It examines how the political cleavage between the 'politics of gratitude' and the 'politics of defiance' shapes northern Cyprus's internal political landscape and ontological security. Focusing on the 2015 election of Mustafa Ak & imath;nc & imath; and Turkey's subsequent intervention in the 2020 elections, this study highlights the challenges faced by emancipatory defiance against a dominant patron. Using Reinhard Wolf's framework of asymmetric deference, the paper demonstrates how gratitude and defiance influence the pursuit of autonomy and identity preservation in client states. The findings contribute to the understanding of the complexities of patron-client relationships in de facto states.
Keywords: Turkey; Northern Cyprus; De Facto States; Patron-client relationship